Pengembangan LKPD Berbasis PBL-STEM sebagai Upaya Peningkatan Berpikir Kreatif Siswa pada Materi Keanekaragaman Hayati SMA/MA - Adisty, Yuda; Manalu, Kartika (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The purpose of this study is to create a Problem-Based Learning (PBL) approach in STEM (Science, Technology, Engineering, and Mathematics) education, specifically in the field of Biology. The goal is to enhance students' creative thinking skills during the study of biodiversity. The Student Worksheets (LKPD) developed are intended to be valid, practical, and effective. This study involves research and development activities using the 4-D model consisting of defining, designing, developing, and disseminating stages. The research was conducted at Muhammadiyah 8 High School Kisaran during the academic year 2023/2024. Data collection was carried out using validation sheets, student questionnaires, and testing devices. Subsequently, data were collected using the N-Gain formula. The PBL-STEM based LKPD was deemed valid by media validators with 96% agreement, material validators with 89%, and instrument validators with 95%. Feasibility analysis showed that the PBL-STEM based LKPD produced is highly practical for student use, as evidenced by a high N-Gain score of 0.92. This study concludes that the developed PBL-STEM based LKPD is valid, practical, and useful in enhancing students' creative thinking abilities.